The Writing Workshop A Course Outline - Collins, James L.; Moran, Charles ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
A sequential series of writing assignments designed and tested for a tenth grade writing workshop through the cooperative efforts of college and technical high school English teachers is discussed in this paper. Twelve assignments and their underlying educational theories are explained. The first six assignments are described as progressive and cumulative, with six specific learning objectives: (1) describe an object, (2) describe a place, (3) describe a person, (4) tell something that happened to you, (5) tell about something you saw happen, and (6) describe a neighborhood that you know well. Assignments 7 through 12 are offered for teachers to choose from at random: (7) explain how to do something; (8) explain how something works; (9) explain why you do or did something; (10) select a picture and describe what you see and what you think about it; (11) select a passage from a book, read it through, and explain what you read and what you think about it; and (12) persuade someone to agree with what you think about something. Successful strategies that have helped students who were unable to find a subject are also suggested. (AEA)
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Assignments; Basic Skills; College School Cooperation; Course Descriptions; Creative Writing; Expository Writing; Secondary Education; Sequential Approach; Skill Development; Teaching Methods; Writing (Composition); Writing Exercises; Writing Instruction; Reports, Descriptive